Towards a New Canon: Ensayo sobre la literatura inglesa (1881) and the Reception of English Literature in Spain in the Nineteenth Century - Medina Calzada, Sara (Estudios Humanísticos. Filología, 2014)
Resumen Este artículo analiza Ensayo sobre la literatura inglesa, obra de Joaquín Henrich y Girona publicada en 1881 que puede considerarse la primera historia completa de la literatura inglesa escrita en español. Su publicación se enmarca en una fase de la recepción de la literatura inglesa en España en la que crece el conocimiento y el interés por esta literatura y, como consecuencia, se configura un nuevo canon literario inglés. Palabras clave: historiografía literaria, canon, recepción de literatura inglesa en España, siglo XIX. Abstract This paper examines Joaquín Henrich y Girona’s Ensayo sobre la literatura inglesa (1881), the first complete history of English literature written in Spanish. Published at a time when the knowledge and interest in English writers was increasing in Spain, Henrich’s work is part of the process of formation of a new and wider English canon that was taking place in the last decades of the nineteenth century. Key words: literary historiography, canon, reception of English literature in Spain, nineteenth century.